God Bothering Beckett. (26th December 2020) - Conti, Christopher
Abstract: In this article I consider the bearing of theology on Samuel Beckett's work in terms of what he called 'the shape' of the idea. At the heart of Beckett's negative aesthetic program is the relation of art to truth. The Beckettian subject and object are the remnants of a denarration that foregrounds the pains his narrators endure on their quest for aseity or inexistence. The narrative struggle to tell a story that cannot be told without falsifying it entails a relation to the absolute centring on the experience of incomprehensibility and pain. In Beckett, God can no more come to expression than the self, making the connection between the two impossibilities all but inescapable.